MOTIF IDEOLOGI, POLITIK, KEAMANAN: TINJAUAN ASPEK PEMBUKTIAN DALAM TINDAK PIDANA TERORISME DI INDONESIA - Saragih, Yasmirah Mandasari; Assegaf, Tengku Muhammad Reza Fikri Dharmawan; Pangaribuan, Christine Natalia; Aruan, Yulia Christy Shintara; Silalahi, Bonari Tua (Collegium Studiosum Journal, 2025)
Law Number 5 of 2018 concerning Terrorism (Law No. 5/2018) incorporates the element of motive ideology, politics, or security disturbance within the definition of terrorism, signifying a crucial assertion in Indonesian penal policy. This research, employing a normative juridical method with statutory, conceptual, and limited secondary data-based case analysis approaches, scrutinizes the fundamental problematics associated with said motive element. The findings indicate that the absence of an operational definition for the motive phrase in the Law's elucidation engenders ambiguity. Regarding its legal status, it remains debatable whether it functions as a general qualification or a constitutive element of the offense (delict) that necessitates proof under each criminal provision. Furthermore, the substantiation of subjective motive presents a significant challenge in judicial practice. Consequently, the implementation of this motive element potentially fosters legal uncertainty and the risk of subjectivity in law enforcement. This study recommends limited amendments to the Law, the issuance of interpretative guidelines by the Supreme Court, and internal directives for law enforcement agencies to ensure legal certainty and the observance of Human Rights in combating terrorism.